Development of a comprehensive health-risk prediction tool for postmenopausal women. Issue 12 (December 2019) - Hedlin, Haley; Weitlauf, Julie; Crandall, Carolyn J.; Nassir, Rami; Cauley, Jane A.; Garcia, Lorena; Brunner, Robert; Robinson, Jennifer; Stefanick, Marica L.; Robbins, John
Abstract: Objective: The aim of the study was to develop a web-based calculator that predicts the likelihood of experiencing multiple, competing outcomes prospectively over 5, 10, and 15 years. Methods: Baseline demographic and medical data from a healthy and racially and ethnically diverse cohort of 161, 808 postmenopausal women, aged 50 to 79 at study baseline, who participated in the Women's Health Initiative (WHI), were used to develop and evaluate a risk-prediction calculator designed to predict individual risk for morbidity and mortality outcomes. Women were enrolled from 40 sites arranged in four regions of the United States. The calculator predicts all-cause mortality, adjudicated outcomes of health events (ie, myocardial infarction [MI], stroke, and hip fracture), and disease (lung, breast, and colorectal cancer). A proportional subdistribution hazards regression model was used to develop the calculator in a training dataset using data from three regions. The calculator was evaluated using the C-statistic in a test dataset with data from the fourth region. Results: The predictive validity of our calculator measured by the C-statistic in the test dataset for a first event at 5 and 15 years was as follows: MI 0.77, 0.61, stroke 0.77, 0.72, lung cancer 0.82, 0.79, breast cancer 0.60, 0.59, colorectal cancer 0.67, 0.60, hip fracture 0.79, 0.76, and death 0.74, 0.72. Conclusion: This study represents the first large-scale study to develop a risk prediction calculator that yields health risk prediction for several outcomes simultaneously. Development of this tool is a first step toward enabling women to prioritize interventions that may decrease these risks. N/A: Video Summary: http://links.lww.com/MENO/A463 . Abstract : Supplemental Digital Content is available in the text